Law Enforcement of Social Distancing Violations and Their Implications Regarding Covid-19 Prevention As Regulated in Law Number 6 of 2018 Concerning Health Quarantine - Moh Arif Haryanto; Faisal Santiago; Suparno Suparno (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
The COVID-19 pandemic is becoming an international threat. In order to overcome this, the Indonesian government has implemented a social distancing policy. However, the realization of the policies that exist to date has not run uniformly in relation to social distancing and social assistance that has not been received directly by the community. Therefore it is necessary to control the implementation process of policies that have been issued by the Government. This research is a normative legal research and empirical law with a normative juridical approach. The data obtained in this research is in the form of literature study and interviews. The data that has been collected is then presented in the form of descriptions which are arranged systematically following the flow of systematic discussion.